2017
DOI: 10.1080/14737167.2017.1292852
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of vildagliptin for people with type 2 diabetes mellitus in Brazil; findings and implications

Abstract: Vildagliptin is an inhibitor of the enzyme dipeptidyl peptidase 4, indicated for the treatment of type 2 diabetes mellitus, combined or not with metformin. This study aims to evaluate the cost-effectiveness of vildagliptin in the Brazilian context. Areas covered: Using MEDLINE, Cochrane Library, Lilacs and CRD, six studies were selected for the economic models. This study utilised cost data in the Brazilian health system to provide the context. Expert commentary: Type 2 diabetes mellitus is an epidemic disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Patients treated with IGla in our study did not have adequate HbA1c control. Our findings are similar to those found by Marra et al (2017) (72) and Souza el al (2015) (43), with more than 60% of patients with poor control of HbA1c which again can be different from other published studies. Two other Brazilian studies (73,74) also found poor glycemic control in DM patients, which needs to be addressed going forward.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Patients treated with IGla in our study did not have adequate HbA1c control. Our findings are similar to those found by Marra et al (2017) (72) and Souza el al (2015) (43), with more than 60% of patients with poor control of HbA1c which again can be different from other published studies. Two other Brazilian studies (73,74) also found poor glycemic control in DM patients, which needs to be addressed going forward.…”
Section: Discussionsupporting
confidence: 86%
“…Type 1 Diabetes Mellitus (T1DM) is a chronic, costly disease, both for people living with T1DM and for governments and society (1,2). The economic burden of T1DM is largely due to the costs of medicines and the complications of diabetes (3,4), with the different insulins differing in terms of their pharmacokinetic parameters as well as costs (5).…”
Section: Introductionmentioning
confidence: 99%
“…• HTA can contribute to such analyses [129]. However, different methods may be needed to fully incorporate the benefits and value of new medicines for cancer into future pricing considerations given affordability constraints that exist within countries, especially LMICs.…”
Section: Buyers (Including Health Authorities and Patients)mentioning
confidence: 99%
“…Diabetes mellitus (DM) is a chronic and complex disease that requires continuous medical care. DM can be subdivided into several etiological types, with Type 1 DM (T1DM) and Type 2 DM (T2DM) being the most prevalent [ 1 ]. T1DM is characterized by the destruction of the islets of Langerhans and insulin-secreting β1 cells in the pancreas mediated by the immune response, and its treatment is based on the replacement of deficient or non-existent insulin [ 2 ].…”
Section: Introductionmentioning
confidence: 99%